Telescope Mirror Cleaning Using Atmospheric Pressure Multi-Channel Radio Frequency Plasma Jet - Yaseen, Waleed Ibrahim; Al-Shakarchi, Duraid A. (Iraqi Journal of Science, 2024)
In this work, the surface of the telescope’s mirror is cleaned using an atmospheric-pressure radio frequency plasma jet (APRFPJ), which is generated by Argon gas between two coaxial metal electrodes. The RF power supply is set to 2 MHz frequencies with three different power levels: 20, 50, and 80 W. Carbon, that has adhered to the surface, can be effectively removed using the plasma cleaning technique, which also modifies any residual bonds. The cleaned surface was clearly distinguished using an optical emission spectroscopy (OES) technique and a water contact angle (WCA) analyzer for the activation property on their surfaces. The sample showed a super hydrophilic surface at an angle of 1° after 2.5 minutes of plasma treatment, as determined by the WCA technique, and an analysis of its optical properties showed that its reflectance had increased from 75% before cleaning to 98% after cleaning. Using the OES technique, the RF plasma jet’s spectrum can be observed to contain the ArI, ArII, and NI lines.